Penerapan Model Pembelajaran Contextual Teaching and Learning (CTL) dalam Meningkatkan Minat Belajar Siswa Kelas VII SMP Negeri 2 Botomuzoi - Lase, Hasatulo; Laoli, Bezisokhi; Harefa, Yearning; Lase, Asali (Jurnal Tematik, 2025)
This study aims to improve students’ learning interest through the application of the Contextual Teaching and Learning (CTL) model in Social Studies (IPS) for Grade VII students at SMP Negeri 2 Botomuzoi in the 2024/2025 academic year. The main issue addressed is the low level of student interest in learning due to the use of monotonous conventional teaching methods and the suboptimal implementation of the CTL model by teachers. The research employed a Classroom Action Research (CAR) method conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Data collection instruments included teacher and student observation sheets, student learning interest questionnaires, and learning outcome tests. The results showed a significant increase in students’ learning interest and academic performance. Teacher observation scores improved from 61.66% in the first cycle to 93.33% in the second cycle, student observations increased from 58.92% to 89.44%, student learning interest rose from 61.09% to 93.79%, and learning mastery improved from 46.88% to 100%. These findings indicate that the CTL model is effective in enhancing students’ interest and academic outcomes. Therefore, CTL is recommended as an alternative instructional strategy to create meaningful and contextual learning experiences in Social Studies.